Efek Internet of Things Terhadap Pelaksanaan Tugas, Prestasi dan Kinerja Guru Sekolah Dasar Berdasarkan Gender dan Usia - Ahmad Nasir (LPPM Universitas Pendidikan Mandalika, 2021)
This study aims to analyze the differences in the influence of internet use on the implementation of tasks, achievements, and performance of male and female elementary school teachers in Wonosalam District, Demak Regency. The method used in this research was ex post facto. The sampling technique used cluster random sampling with two-stage cluster sampling. The data analysis technique used was descriptive statistical analysis. The data analysis technique used a questionnaire and documentation. The results of this study indicate that the internet used by teachers was not dominated only by one gender. Both genders had equal understanding and access to the internet. This was because the respondents were academics who had the same high exposure to technology. Academic activities that require teachers who are able to adapt to technology that makes them have almost equal technological capabilities.